The zoogeography of the cetaceans in Algoa Bay - Melly, Brigitte Leigh (Rhodes University, Faculty of Science, Department of Geography, 2011)
The most recent study on cetaceans in Algoa Bay, South Africa, was conducted over 14 years ago. Consequently, knowledge of the cetacean species visiting this bay is currently based on incidental observations and stranding data. A number of developments in recent years: a deepwater port, proposed oil refinery, increased boating and fishing (commercial and recreational), a proposed Marine Protected Area, and the release of a whale-watching permit, all of which may impact these animals in some way, highlight the need for a baseline study on cetaceans. Therefore, the aim of this study was to determine the spatial and temporal distribution, and habitat preference of cetaceans in Algoa Bay. Boat-based surveys were conducted monthly between March 2009 and July 2010. At each sighting the GPS location, species, group size and composition, and behaviour were recorded. Using GIS, the sighting data was related to data layers of geographical variables such as sea surface temperature, depth and sea-floor substrate. Approximately 365 hours of search effort were completed over 57 surveys, with a total of 346 sightings. Species observed were: southern right whales (Eubalaena australis), humpback whales (Megaptera novaeangliae), Bryde's whales (Balaenoptera brydei), Indian Ocean bottlenose dolphins (Tursiops aduncus), Indo-Pacific humpback dolphins (Sousa chinensis), and longbeaked common dolphins (Delphinus capensis). Southern right whales were observed during austral winter, utilising the shallow, protected areas of the bay as a mating and nursery ground. Humpback whales were also recorded extensively during winter, in more offshore waters, with a significant number of mother-calf pairs sighted. Bryde's whales were recorded in offshore waters during summer and autumn, where they were primarily observed travelling and foraging. Bottlenose dolphins were the most prolific species sighted. They were recorded year-round throughout the inshore waters of the bay, with large group sizes (up to 500 animals), and displayed a wide variety of behaviours. Humpback dolphins were observed in extremely shallow and inshore waters (mean bottom depth of 6.6 m) along the south-west corner of the bay, in small groups of approximately three individuals. Common dolphins were the least observed species, and were mainly observed foraging in large groups of up to 800 individuals. The results of this study indicate how cetaceans utilise the bay in significantly different ways. Geographical and anthropogenic factors have influenced the spatial and temporal distribution of these animals and have resulted in habitat preferences, as well as potential key habitats, in the bay. Thus, this study has provided baseline information for future research and for better informed conservation and management strategies in Algoa Bay.
Keywords: Cetacea -- South Africa -- Algoa Bay; Cetacea -- Behavior -- South Africa -- Algoa Bay; Cetacea -- South Africa -- Algoa Bay -- Geographical distribution; Cetacea -- Counting -- South Africa -- Algoa Bay